A method for balancing the transverse and longitudinal shrinkage of glass fiber reinforced thermoplastic composite materials

By blending the treated biomass-based carbon tube with thermoplastic resin and glass fibers, a hollow tubular structure is formed, which solves the problem of warping of glass fiber-reinforced thermoplastic composite materials, and reduces the material strength and specific gravity without changing. The effect of warpage.

CN118952499BActive Publication Date: 2025-01-03QIHE TECH (JILIN) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411444193.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-03
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

Existing glass fiber reinforced thermoplastic composite materials often experience warping problems in products, resulting in low product qualification rate. When reducing the glass fiber content or using inorganic minerals to balance the shrinkage rate, the material strength decreases, making it difficult to ensure that the specific gravity remains unchanged. In the case, the warpage is reduced and the high strength is maintained at the same time.

Method used

Using biomass-based carbon tube material, it is treated with silane coupling agent and blended with thermoplastic resin and glass fiber to form a hollow tubular structure. The "anchor point" effect is used to reduce the orientation of glass fibers during injection molding, and balance the horizontal and verticality of the composite material. Shrinkage and improve material compatibility to reduce warpage.

Benefits of technology

While ensuring that the specific gravity of the composite material remains unchanged, the warpage of the product is effectively reduced, and the strength of the material is improved, avoiding the strength decrease when using inorganic minerals to replace glass fiber, achieving a balance between high strength and low warping Effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118952499B_ABST
    Figure CN118952499B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of glass fiber reinforced thermoplastic materials, and relates to a method for balancing the transverse and longitudinal shrinkage of glass fiber reinforced thermoplastic composite materials, including selecting suitable biomass-based carbon tubes for processing; weighing thermoplastic resin and compatibilizer into a stirring pot and stirring evenly; adding a wetting agent into the stirring pot and stirring evenly; adding a processing aid into the stirring pot and stirring evenly at a low speed, and then adding the mixed material into the main feed loss-in-weight scale; after the biomass-based carbon tube fiber and the glass fiber are stirred evenly at a low speed, they are added into the side feed loss-in-weight scale. Since the biomass-based carbon tube fiber material is relatively light, it is mixed with glass fiber for use; the feeding amount of each loss-in-weight scale is set, the appropriate screw speed is set, the auxiliary equipment is turned on, and granulation production is carried out. This method is superior to the method of replacing part of the glass fiber with inorganic minerals of special microscopic shapes to balance the shrinkage of the composite material, and can keep the mass proportion of the positive glass fiber unchanged under the condition of unchanged specific gravity, thereby ensuring the strength of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass fiber reinforced thermoplastic materials, and specifically relates to a method for balancing the transverse and longitudinal shrinkage rates of a glass fiber reinforced thermoplastic composite material using a biomass-based carbon tube material, which is suitable for reducing the warpage of an injection molded product. Background Art

[0002] At present, high-strength glass fiber reinforced thermoplastic materials are the mainstream products in the market, but the large-scale products of glass fiber reinforced thermoplastic composite materials are often warped and deformed, resulting in a low product qualification rate, which reduces production efficiency and increases product manufacturing costs. At present, when researchers modify glass fiber reinforced thermoplastic composite materials, they mainly reduce the glass fiber content and add some spherical, flaky, star-shaped, and granular inorganic minerals. Under the condition of ensuring the same specific gravity, the horizontal (vertical direction) and vertical (flow direction) shrinkage rates of the composite materials can be slightly improved, thereby improving the product qualification rate. However, the reduction in glass fiber content will reduce the overall strength of the composite material.

[0003] With the improvement of people's living standards, the speed of product replacement is getting faster and faster, and the requirements for product quality are gradually increasing, which puts higher requirements on scientific researchers. Under the condition of ensuring that the specific gravity of composite materials remains unchanged, high-strength and high-quality products are the mainstream of composite material development. The prior art discloses a polyphenylene sulfide composite material for a high-filled low-warpage battery module end plate and a preparation method thereof. The weight percentage of the polyphenylene sulfide composite material is composed of: 35-55% polyphenylene sulfide resin, 40-50% flat glass fiber, 5-15% glass microspheres, 3-7% toughening agent, 0.2-0.5% compatibilizer, 0.1-0.5% antioxidant, and 0.2-1.0% lubricant. Glass microspheres, inorganic minerals, and flat glass fibers are introduced into the material to jointly reinforce the polyphenylene sulfide resin. The unique spherical structure of the glass microspheres can reduce the orientation of the glass fibers during injection molding, thereby reducing the difference in shrinkage rate between the flow direction and the vertical flow direction of the product, and improving the qualified product rate. However, since the reinforcing skeleton of glass fiber reinforced composite materials is mainly glass fiber, the method of replacing part of the glass fiber with inorganic minerals will reduce the strength of the material under the same specific gravity. At this time, the strength of the material will inevitably decrease. The prior art also discloses a low-warpage reinforced PC / ABS alloy material and its preparation method. The reinforced PC / ABS alloy material is made of components in weight percentage: 70 parts of PC resin, 20 parts of ABS resin, 10 parts of glass fiber, 1 part of four-needle zinc oxide whisker, 0.4 parts of antioxidant, and 0.2 parts of lubricant. This method introduces four-needle zinc oxide whiskers (unique four-needle structure) into the reinforced PC / ABS alloy material system, which can change the orientation of the glass fiber and reduce the orientation degree of the glass fiber along the flow direction, thereby balancing the horizontal (vertical direction) and longitudinal (flow direction) shrinkage rates of the product and reducing the warpage of the product. However, if some minerals are used to replace glass fibers, the overall strength of the material will also decrease.

[0004] Based on this, there is an urgent need to develop a new method to balance the transverse and longitudinal shrinkage rates of glass fiber reinforced thermoplastic composites, so that the transverse (vertical direction) and longitudinal (flow direction) shrinkage rates can be balanced while ensuring that the specific gravity of the composite material remains unchanged, and the warping of the product can be reduced to meet current usage requirements. Summary of the invention

[0005] The purpose of the present invention is to provide a method for balancing the shrinkage rates of glass fiber reinforced thermoplastic composite materials in the vertical direction and the flow direction using biomass-based carbon tube materials, so as to solve the problem of balancing the transverse and longitudinal shrinkage rates while ensuring that the specific gravity of the composite material remains unchanged and reducing the warping of the product.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] A method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material comprises the following steps:

[0008] A. Select biomass-based carbon tubes for treatment. The selected biomass-based carbon tubes have a length of 0.01-0.1 mm and are fibrous materials with a fiber diameter of 15-30 microns;

[0009] The processing method of biomass-based carbon tubes is:

[0010] A1. Place the biomass-based carbon tubes in a drying oven at 80°C and a vacuum degree of -0.08Mpa for 12 hours;

[0011] A2. Mix the silane coupling agent with 99% alcohol in a ratio of 1:1 and stir for 5 minutes.

[0012] A3, ultrasonically dispersing the biomass-based carbon tubes obtained in step A1 into the proportioned solution of silane coupling agent and alcohol prepared in step A2, and ultrasonically dispersing them uniformly;

[0013] A4, vacuum filter the biomass-based carbon tubes wrapped with the ratio liquid, and then put them into a vacuum oven at 65°C for 4 hours for standby use;

[0014] B. Weigh a certain amount of thermoplastic resin and a certain amount of compatibilizer and put them into a stirring pot, stir for 5 minutes until they are evenly stirred;

[0015] C. Add a certain amount of wetting agent into the stirring pot and stir for 5 minutes until it is evenly stirred;

[0016] D. Add a certain amount of processing aids to the mixing pot, stir at a low speed for 5 minutes, stir evenly, and then add the mixed materials into the main feed weight loss scale;

[0017] E. The biomass-based carbon tubes and chopped glass fibers treated in step A are stirred evenly at a low speed and then added to a side-feed weight loss scale; since the biomass-based carbon tube fiber material is relatively light and cannot be fed smoothly, it is mixed with glass fibers for use;

[0018] F. Set the feeding amount of each loss-in-weight scale, set the appropriate screw speed, start the auxiliary equipment, and carry out granulation production;

[0019] In parts by weight, the thermoplastic resin is 50-70, the chopped glass fiber is 20-30, the compatibilizer is 3-5, the treated biomass-based carbon tube is 3-10, the processing aid is 0.5-1.5, and the wetting agent is 0.3-1.2.

[0020] Furthermore, in step A, the biomass-based carbon tubes are vascular bundle materials extracted from straw, bamboo, and trees as basic raw materials.

[0021] Furthermore, in step B, the thermoplastic resin is at least one of PP, PA, PC, PBT, PET, and ABS.

[0022] Furthermore, in step C, the wetting agent is one of white oil, diffusion oil and silicone oil.

[0023] Furthermore, in step D, the processing aid includes an antioxidant and a lubricant; wherein the antioxidant is composed of hindered phenols and phosphites, the hindered phenols and phosphites antioxidants are compounded in a ratio of 1:2, the hindered phenols are at least one of 1010, 1076, and 1098, and the phosphites are at least one of 168 and 626; the lubricant is at least one of EBS, PETS, stearic acid, stearate, and PE wax.

[0024] Furthermore, in step E, the chopped glass fibers are alkali-free chopped glass fibers impregnated with a silane coupling agent, and have a diameter of 9 microns to 14 microns.

[0025] Furthermore, the compatibilizer is a substance with a polar group, specifically thermoplastic resin grafted with maleic anhydride, ethylene-acrylate-glycidyl methacrylate terpolymer, and acrylate grafted with ethylene elastomer.

[0026] Furthermore, in step E, the screw speed is 380-400 rpm.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The present invention provides a method for balancing the transverse (vertical direction) and longitudinal (flow direction) shrinkage of glass fiber reinforced thermoplastic composite materials by using biomass-based carbon tube materials. The method is superior to the method of replacing part of the glass fiber with inorganic minerals of special microscopic shapes to balance the transverse (vertical direction) and longitudinal (flow direction) shrinkage of the composite material. The method can ensure that the mass ratio of the glass fiber remains unchanged when the specific gravity of the composite material changes very little, thereby ensuring the strength of the composite material.

[0029] 2. In the present invention, the ports of the hollow tubular biomass-based carbon tube material form "anchor points" with the thermoplastic material, thereby forming "physical crosslinking"; when the composite material is injection molded, the small-sized biomass-based carbon tube fiber has a relatively small aspect ratio and will not form orientation; after the hollow tubular biomass-based carbon tube fiber is treated with a silane coupling agent, its compatibility with the thermoplastic material is improved; thus, all the "anchor points" will fasten the glass fiber in the anchor point cage, reduce the orientation of the glass fiber inside the composite material during injection molding, balance the shrinkage rate in the transverse (vertical direction) and longitudinal (flow direction), and reduce the warpage of the product;

[0030] 3. The ends of the hollow tubular biomass-based carbon tube materials are blocked by thermoplastic materials to form partial hollowness. Therefore, when adding a suitable proportion, the specific gravity of the composite material will not be greatly changed. The composite material produced is stronger than the method of replacing glass fiber with part of inorganic minerals. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0032] Figure 1 Flow chart of the processing steps for coupling agent impregnation of biomass-based carbon tubes. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with embodiments:

[0034] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. It is to be understood that the specific embodiments described herein are only used to explain the present invention, rather than to limit the present invention. It should also be noted that, for ease of description, only parts related to the present invention, rather than all structures, are shown in the accompanying drawings.

[0035] It should be noted that similar reference numerals and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings. At the same time, in the description of the present invention, the terms "first", "second", etc. are only used to distinguish the description and cannot be understood as indicating or implying relative importance.

[0036] It should be specially noted that if no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or in the product instructions shall be followed. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be obtained commercially.

[0037] Biomass-based carbon tube materials are micron-sized materials produced from plant vascular bundles, and their microstructure is hollow tubular. In the present invention, biomass-based carbon tube materials are treated with silane coupling agents and co-extruded with thermoplastic materials, compatibilizers, and glass fibers to solve the warping problem caused by the large difference in shrinkage rates in the horizontal (vertical direction) and vertical (flow direction) directions of the material. The principles are as follows:

[0038] 1. The ends of the hollow tubular biomass-based carbon tube materials form "anchor points" with the thermoplastic material, thereby forming "physical cross-linking";

[0039] 2. When the composite material is injected, the small-sized biomass-based carbon tube fiber has a relatively small aspect ratio and will not form orientation;

[0040] 3. After the hollow tubular biomass-based carbon tube fiber is treated with a silane coupling agent, its compatibility with thermoplastic materials is improved.

[0041] Through the simultaneous action of the above three points, all the "anchor points" will fasten the glass fiber in the anchor cage, reduce the orientation of the glass fiber inside the composite material during injection molding, balance the horizontal (vertical direction) and longitudinal (flow direction) shrinkage rates, and reduce the warpage of the product. The ports of the hollow tubular biomass-based carbon tube material are blocked by thermoplastic materials to form a partial hollow, so when adding the appropriate proportion, it will not change the specific gravity of the composite material. The composite material produced is stronger than the method of replacing glass fiber with part of the mineral powder.

[0042] The method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material of the present invention comprises the following steps:

[0043] A. Select appropriate biomass-based carbon tubes for processing. The biomass-based carbon tubes are vascular bundle materials extracted from straw, bamboo, trees, etc., and commercially available finished products are sufficient. The length of the biomass-based carbon tubes is 0.01-0.1mm, and they are fibrous materials with a fiber diameter between 15-30 microns.

[0044] The processing method of biomass-based carbon tubes is:

[0045] A1. Place the biomass-based carbon tubes in a drying oven at 80°C and a vacuum degree of -0.08Mpa for 12 hours;

[0046] A2. Mix the silane coupling agent with 99% alcohol in a ratio of 1:1 and stir for 5 minutes.

[0047] A3, ultrasonically dispersing the biomass-based carbon tubes obtained in step A1 into the proportioned solution of silane coupling agent and alcohol prepared in step A2, and ultrasonically dispersing them uniformly;

[0048] A4. The biomass-based carbon tubes wrapped with the formulation liquid are vacuum filtered and then placed in a vacuum oven at 65°C for 4 hours for use.

[0049] B. Weigh a certain amount of thermoplastic resin and a certain amount of compatibilizer and put them into a stirring pot, stir for 5 minutes until they are evenly mixed.

[0050] C. Add a certain amount of wetting agent into the mixing pot and stir for 5 minutes until it is evenly mixed.

[0051] D. Add a certain amount of processing aid to the mixing pot, stir at low speed for 5 minutes to mix evenly, and then add the mixed materials into the main feed loss-in-weight scale.

[0052] E. The biomass-based carbon tubes and chopped glass fibers treated in step A are stirred evenly at a low speed and then added to a side-feed loss-in-weight scale. Since the biomass-based carbon tube fiber material is relatively light and cannot be fed smoothly, it is mixed with glass fibers for use.

[0053] F. Set the feeding amount of each loss-in-weight scale, set the appropriate screw speed, turn on the auxiliary equipment, and carry out granulation production.

[0054] In step B, the thermoplastic resin is at least one of PP, PA, PC, PBT, PET, and ABS.

[0055] In step C, the wetting agent is one of white oil (No. 3, No. 5, No. 7, No. 10, No. 15, No. 32, No. 68), diffusion oil, and silicone oil.

[0056] Step D, the processing aid includes an antioxidant and a lubricant. The antioxidant is composed of hindered phenols and phosphites. The hindered phenols and phosphites are compounded in a ratio of 1:2, the hindered phenols are at least one of 1010, 1076, and 1098, and the phosphites are at least one of 168 and 626. The lubricant is at least one of EBS, PETS, stearic acid, stearate, and PE wax.

[0057] In step E, the glass fiber is common alkali-free chopped glass fiber impregnated with a silane coupling agent on the market, and has a diameter of 9 microns to 14 microns.

[0058] The compatibilizer is a substance with polar groups, specifically thermoplastic resin grafted with maleic anhydride, ethylene-acrylate-glycidyl methacrylate terpolymer, and acrylate grafted with ethylene elastomer.

[0059] Specifically, in parts by weight, the thermoplastic resin is 50-70, the chopped glass fiber is 20-30, the compatibilizer is 3-5, the treated biomass-based carbon tube is 3-10, the processing aid is 0.5-1.5, and the wetting agent is 0.3-1.2.

[0060] Embodiment 1: A method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material, comprising the following steps:

[0061] A. Select biomass-based carbon tubes with a length of 0.01-0.1 mm and a fiber diameter of 15-30 microns and perform the following treatment:

[0062] A1. Place the biomass-based carbon tubes in a drying oven at 80°C and a vacuum degree of -0.08Mpa for 12 hours;

[0063] A2. Mix the silane coupling agent with 99% alcohol in a ratio of 1:1 and stir for 5 minutes.

[0064] A3, ultrasonically dispersing the biomass-based carbon tubes obtained in step A1 into the proportioned solution of silane coupling agent and alcohol prepared in step A2, and ultrasonically dispersing them uniformly;

[0065] A4. The biomass-based carbon tubes wrapped with the formulation liquid are vacuum filtered and then placed in a vacuum oven at 65°C for 4 hours for use.

[0066] B. Weigh a certain amount of PA6 and a certain amount of compatibilizer and put them into a stirring pot. Stir for 5 minutes until they are evenly mixed.

[0067] C. Add a certain amount of wetting agent into the mixing pot and stir for 5 minutes until it is evenly mixed.

[0068] D. Add a certain amount of processing aid to the mixing pot, stir at low speed for 5 minutes to mix evenly, and then add the mixed materials into the main feed loss-in-weight scale.

[0069] E. The biomass-based carbon tubes and chopped glass fibers treated in step A are stirred evenly at a low speed and then added to a side-feed loss-in-weight scale. Since the biomass-based carbon tube fiber material is relatively light and cannot be fed smoothly, it is mixed with glass fibers for use.

[0070] F. Set the feeding amount of each loss-in-weight scale, set the appropriate screw speed, turn on the auxiliary equipment, and carry out granulation production.

[0071] Specifically, in parts by weight, PA6 is 63, short glass fiber is 30, compatibilizer is 4, treated biomass-based carbon tube is 7, processing aid is 0.8, and wetting agent is 0.4.

[0072] Embodiment 2: A method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material, comprising the following steps:

[0073] A. Select biomass-based carbon tubes with a length of 0.01-0.1 mm and a fiber diameter of 15-30 microns and perform the following treatment:

[0074] A1. Place the biomass-based carbon tubes in a drying oven at 80°C and a vacuum degree of -0.08Mpa for 12 hours;

[0075] A2. Mix the silane coupling agent with 99% alcohol in a ratio of 1:1 and stir for 5 minutes.

[0076] A3, ultrasonically dispersing the biomass-based carbon tubes obtained in step A1 into the proportioned solution of silane coupling agent and alcohol prepared in step A2, and ultrasonically dispersing them uniformly;

[0077] A4. The biomass-based carbon tubes wrapped with the formulation liquid are vacuum filtered and then placed in a vacuum oven at 65°C for 4 hours for use.

[0078] B. Weigh a certain amount of PA6 and a certain amount of compatibilizer and put them into a stirring pot. Stir for 5 minutes until they are evenly mixed.

[0079] C. Add a certain amount of wetting agent into the mixing pot and stir for 5 minutes until it is evenly mixed.

[0080] D. Add a certain amount of processing aid to the mixing pot, stir at low speed for 5 minutes to mix evenly, and then add the mixed materials into the main feed loss-in-weight scale.

[0081] E. The biomass-based carbon tubes and chopped glass fibers treated in step A are stirred evenly at a low speed and then added to a side-feed loss-in-weight scale. Since the biomass-based carbon tube fiber material is relatively light and cannot be fed smoothly, it is mixed with glass fibers for use.

[0082] F. Set the feeding amount of each loss-in-weight scale, set the appropriate screw speed, turn on the auxiliary equipment, and carry out granulation production.

[0083] Specifically, in parts by weight, the PA6 is 61, the chopped glass fiber is 30, the compatibilizer is 4, the treated biomass-based carbon tube is 5, the processing aid is 0.8, and the wetting agent is 0.4.

[0084] Embodiment 3: A method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material, comprising the following steps:

[0085] A. Select biomass-based carbon tubes with a length of 0.01-0.1 mm and a fiber diameter of 15-30 microns and perform the following treatment:

[0086] A1. Place the biomass-based carbon tubes in a drying oven at 80°C and a vacuum degree of -0.08Mpa for 12 hours;

[0087] A2. Mix the silane coupling agent with 99% alcohol in a ratio of 1:1 and stir for 5 minutes.

[0088] A3, ultrasonically dispersing the biomass-based carbon tubes obtained in step A1 into the proportioned solution of silane coupling agent and alcohol prepared in step A2, and ultrasonically dispersing them uniformly;

[0089] A4. The biomass-based carbon tubes wrapped with the formulation liquid are vacuum filtered and then placed in a vacuum oven at 65°C for 4 hours for use.

[0090] B. Weigh a certain amount of PA6 and a certain amount of compatibilizer and put them into a stirring pot. Stir for 5 minutes until they are evenly mixed.

[0091] C. Add a certain amount of wetting agent into the mixing pot and stir for 5 minutes until it is evenly mixed.

[0092] D. Add a certain amount of processing aid to the mixing pot, stir at low speed for 5 minutes to mix evenly, and then add the mixed materials into the main feed loss-in-weight scale.

[0093] E. The biomass-based carbon tubes and chopped glass fibers treated in step A are stirred evenly at a low speed and then added to a side-feed loss-in-weight scale. Since the biomass-based carbon tube fiber material is relatively light and cannot be fed smoothly, it is mixed with glass fibers for use.

[0094] F. Set the feeding amount of each loss-in-weight scale, set the appropriate screw speed, turn on the auxiliary equipment, and carry out granulation production.

[0095] Specifically, in parts by weight, PA6 is 59, short glass fiber is 30, compatibilizer is 4, treated biomass-based carbon tube is 7, processing aid is 0.8, and wetting agent is 0.4.

[0096] Embodiment 4: A method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material, comprising the following steps:

[0097] A. Select biomass-based carbon tubes with a length of 0.01-0.1 mm and a fiber diameter of 15-30 microns and perform the following treatment:

[0098] A1. Place the biomass-based carbon tubes in a drying oven at 80°C and a vacuum degree of -0.08Mpa for 12 hours;

[0099] A2. Mix the silane coupling agent with 99% alcohol in a ratio of 1:1 and stir for 5 minutes.

[0100] A3, ultrasonically dispersing the biomass-based carbon tubes obtained in step A1 into the mixed solution of silane coupling agent and alcohol prepared in step A2, and uniformly dispersing by ultrasonication;

[0101] A4. The biomass-based carbon tubes wrapped with the formulation liquid are vacuum filtered and then placed in a vacuum oven at 65°C for 4 hours for use.

[0102] B. Weigh a certain amount of PA6 and a certain amount of compatibilizer and put them into a stirring pot. Stir for 5 minutes until they are evenly mixed.

[0103] C. Add a certain amount of wetting agent into the mixing pot and stir for 5 minutes until it is evenly mixed.

[0104] D. Add a certain amount of processing aid to the mixing pot, stir at low speed for 5 minutes to mix evenly, and then add the mixed materials into the main feed loss-in-weight scale.

[0105] E. The biomass-based carbon tubes and chopped glass fibers treated in step A are stirred evenly at a low speed and then added to a side-feed loss-in-weight scale. Since the biomass-based carbon tube fiber material is relatively light and cannot be fed smoothly, it is mixed with glass fibers for use.

[0106] F. Set the feeding amount of each loss-in-weight scale, set the appropriate screw speed, turn on the auxiliary equipment, and carry out granulation production.

[0107] Specifically, in parts by weight, PA6 is 57, short glass fiber is 30, compatibilizer is 4, treated biomass-based carbon tube is 9, processing aid is 0.8, and wetting agent is 0.4.

[0108] Comparative Example 1: A method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material, comprising the following steps:

[0109] A. Weigh a certain amount of PA6 and a certain amount of compatibilizer and put them into a stirring pot. Stir for 5 minutes until they are evenly mixed.

[0110] B. Add a certain amount of wetting agent into the mixing pot and stir for 5 minutes until it is evenly mixed.

[0111] C. Add a certain amount of processing aid to the mixing pot, stir at low speed for 5 minutes to mix evenly, and then add the mixed materials into the main feed loss-in-weight scale.

[0112] D. Add chopped glass fibers to the side-feed loss-in-weight scale.

[0113] E. Set the feeding amount of each loss-in-weight scale, set the appropriate screw speed, turn on the auxiliary equipment, and carry out granulation production.

[0114] In parts by weight, the PA6 is 66, the chopped glass fiber is 30, the compatibilizer is 4, the processing aid is 0.8, and the wetting agent is 0.4.

[0115] Comparative Example 2: A method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material, comprising the following steps:

[0116] A. Select biomass-based carbon tubes with a length of 0.01-0.1 mm and a fiber diameter of 15-30 microns without surface treatment:

[0117] B. Weigh a certain amount of PA6 and a certain amount of compatibilizer and put them into a stirring pot. Stir for 5 minutes until they are evenly mixed.

[0118] C. Add a certain amount of wetting agent into the mixing pot and stir for 5 minutes until it is evenly mixed.

[0119] D. Add a certain amount of processing aid to the mixing pot, stir at low speed for 5 minutes to mix evenly, and then add the mixed materials into the main feed loss-in-weight scale.

[0120] E. Stir the treated biomass-based carbon fiber tubes and chopped glass fibers at a low speed and add them to the side-feed loss-in-weight scale. Since the biomass-based carbon fiber tube material is light and cannot be fed smoothly, it is mixed with glass fibers.

[0121] F. Set the feeding amount of each loss-in-weight scale, set the appropriate screw speed, turn on the auxiliary equipment, and carry out granulation production.

[0122] In parts by weight, the PA6 is 61, the chopped glass fiber is 30, the compatibilizer is 4, the untreated biomass-based carbon tube is 5, the processing aid is 0.8, and the wetting agent is 0.4.

[0123] Comparative Example 3: A method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material, comprising the following steps:

[0124] A. Select biomass-based carbon tubes with a length of 0.1-1 mm and a fiber diameter of 15-30 microns and perform the following treatment:

[0125] A1. Place the biomass-based carbon tubes in a drying oven at 80°C and a vacuum degree of -0.08Mpa for 12 hours;

[0126] A2. Mix the silane coupling agent with 99% alcohol in a ratio of 1:1 and stir for 5 minutes.

[0127] A3, ultrasonically dispersing the biomass-based carbon tubes obtained in step A1 into the mixed solution of silane coupling agent and alcohol prepared in step A2, and uniformly dispersing by ultrasonication;

[0128] A4. The biomass-based carbon tubes wrapped with the formulation liquid are vacuum filtered and then placed in a vacuum oven at 65°C for 4 hours for use.

[0129] B. Weigh a certain amount of PA6 and a certain amount of compatibilizer and put them into a stirring pot. Stir for 5 minutes until they are evenly mixed.

[0130] C. Add a certain amount of wetting agent into the mixing pot and stir for 5 minutes until it is evenly mixed.

[0131] D. Add a certain amount of processing aid to the mixing pot, stir at low speed for 5 minutes to mix evenly, and then add the mixed materials into the main feed loss-in-weight scale.

[0132] E. Mix the treated biomass-based carbon tubes and chopped glass fibers at a low speed according to the proportion and add them to the side-feed loss-in-weight scale. Since the biomass-based carbon tube fiber material is light and cannot be fed smoothly, it is mixed with glass fibers.

[0133] F. Set the feeding amount of each loss-in-weight scale, set the appropriate screw speed, turn on the auxiliary equipment, and carry out granulation production.

[0134] In parts by weight, the PA6 is 61, the chopped glass fiber is 30, the compatibilizer is 4, the treated biomass-based carbon tube is 5, the processing aid is 0.8, and the wetting agent is 0.4.

[0135] Comparative Example 4: A method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material, comprising the following steps:

[0136] A. Select biomass-based carbon tubes with a length of 1-2 mm and a fiber diameter of 15-30 microns and perform the following treatment:

[0137] A1. Place the biomass-based carbon tubes in a drying oven at 80°C and a vacuum degree of -0.08Mpa for 12 hours;

[0138] A2. Mix the silane coupling agent with 99% alcohol in a ratio of 1:1 and stir for 5 minutes.

[0139] A3, ultrasonically dispersing the biomass-based carbon tubes obtained in step A1 into the mixed solution of silane coupling agent and alcohol prepared in step A2, and uniformly dispersing by ultrasonication;

[0140] A4. The biomass-based carbon tubes wrapped with the formulation liquid are vacuum filtered and then placed in a vacuum oven at 65°C for 4 hours for use.

[0141] B. Weigh a certain amount of PA6 and a certain amount of compatibilizer and put them into a stirring pot. Stir for 5 minutes until they are evenly mixed.

[0142] C. Add a certain amount of wetting agent into the mixing pot and stir for 5 minutes until it is evenly mixed.

[0143] D. Add a certain amount of processing aid to the mixing pot, stir at low speed for 5 minutes to mix evenly, and then add the mixed materials into the main feed loss-in-weight scale.

[0144] E. Mix the treated biomass-based carbon tubes and chopped glass fibers at a low speed according to the proportion and add them to the side-feed loss-in-weight scale. Since the biomass-based carbon tube fiber material is light and cannot be fed smoothly, it is mixed with glass fibers.

[0145] F. Set the feeding amount of each loss-in-weight scale, set the appropriate screw speed, turn on the auxiliary equipment, and carry out granulation production.

[0146] In parts by weight, the PA6 is 61, the chopped glass fiber is 30, the compatibilizer is 4, the treated biomass-based carbon tube is 5, the processing aid is 0.8, and the wetting agent is 0.4.

[0147] Comparative Example 5: A method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material, comprising the following steps:

[0148] A. Select solid glass beads with a diameter between 15-30 microns for the following treatment:

[0149] A1. Place the solid glass beads in a drying oven at 80°C and a vacuum degree of -0.08Mpa for 12 hours;

[0150] A2. Mix the silane coupling agent with 99% alcohol in a ratio of 1:1 and stir for 5 minutes.

[0151] A3, ultrasonically dispersing the solid glass microbeads obtained in step A1 into the proportioned liquid of silane coupling agent and alcohol prepared in step A2, and ultrasonically dispersing them uniformly;

[0152] A4. Vacuum filter the solid glass beads wrapped with the ratio solution, and then put them into a vacuum oven at 65°C for 4 hours for use.

[0153] B. Weigh a certain amount of PA6 and a certain amount of compatibilizer and put them into a stirring pot. Stir for 5 minutes until they are evenly mixed.

[0154] C. Add a certain amount of wetting agent into the mixing pot and stir for 5 minutes until it is evenly mixed.

[0155] D. Add a certain amount of processing aid to the mixing pot, stir at low speed for 5 minutes to mix evenly, and then add the mixed materials into the main feed loss-in-weight scale.

[0156] E. The solid glass microbeads and chopped glass fibers treated in step A are stirred evenly at a low speed and then added to a side-feed loss-in-weight scale.

[0157] F. Set the feeding amount of each loss-in-weight scale, set the appropriate screw speed, turn on the auxiliary equipment, and carry out granulation production.

[0158] In parts by weight, the PA6 is 66, the chopped glass fiber is 25, the compatibilizer is 4, the treated solid glass microspheres are 5, the processing aid is 0.8, and the wetting agent is 0.4.

[0159] Comparative Example 6: A method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material, comprising the following steps:

[0160] The steps of filling the hollow part of biomass-based carbon tubes with silica:

[0161] Add the biomass-based carbon tube material (between 15-30 microns) to the sodium silicate aqueous solution, ultrasonically disperse for 30 minutes, drip an excess of dilute hydrochloric acid (4 mol / L) into the mixture, and a precipitate (H2SiO3) appears. At this time, vacuum filter the mixture to obtain a solid. Heat the solid at 155°C for 10 minutes. At this time, the precipitate (H2SiO3) loses water and turns into silicon dioxide. Disperse the heated solid into the aqueous solution, ultrasonicate for 30 minutes, and use a 5000 mesh filter to filter the mixture to filter out the liquid and nano-scale silicon dioxide, and obtain a biomass-based carbon tube containing silicon dioxide in the hollow tube. Repeat the above operation until the tap density remains unchanged, and set aside for the following steps.

[0162] NaSiO3+2HCl=H2SiO3+2NaClSince silicic acid is insoluble in water, silicic acid crystals can be obtained by filtration. Silicic acid (H2SiO3) loses water when heated to form silicon dioxide.

[0163] A. Select biomass-based carbon tubes containing silica in the pipeline and perform the following treatment:

[0164] A1. Dry the biomass-based carbon tubes containing silicon dioxide in the pipeline in a drying oven at 80°C and a vacuum degree of -0.08Mpa for 12 hours;

[0165] A2. Mix the silane coupling agent with 99% alcohol in a ratio of 1:1 and stir for 5 minutes.

[0166] A3, ultrasonically dispersing the biomass-based carbon tubes containing silicon dioxide in the pipeline obtained in step A1 into the proportioned liquid of silane coupling agent and alcohol prepared in step A2, and ultrasonically dispersing them uniformly;

[0167] A4. The biomass-based carbon tubes containing silicon dioxide in the pipe wrapped with the ratio liquid are vacuum filtered, and then placed in a vacuum oven at 65° C. for 4 hours for use.

[0168] B. Weigh a certain amount of PA6 and a certain amount of compatibilizer and put them into a stirring pot. Stir for 5 minutes until they are evenly mixed.

[0169] C. Add a certain amount of wetting agent into the mixing pot and stir for 5 minutes until it is evenly mixed.

[0170] D. Add a certain amount of processing aid to the mixing pot, stir at low speed for 5 minutes to mix evenly, and then add the mixed materials into the main feed loss-in-weight scale.

[0171] E. The biomass-based carbon tubes containing silicon dioxide and the short-cut glass fibers in the pipeline treated in step A are uniformly stirred at a low speed and then added to a side-feed loss-in-weight scale.

[0172] F. Set the feeding amount of each loss-in-weight scale, set the appropriate screw speed, turn on the auxiliary equipment, and carry out granulation production.

[0173] In parts by weight, the PA6 is 61, the chopped glass fiber is 30, the compatibilizer is 4, the biomass-based carbon tube containing silica in the treated pipe is 5, the processing aid is 0.8, and the wetting agent is 0.4.

[0174] The present invention provides the composition ratios of Examples 1-4, as shown in Table 1 (in parts by weight):

[0175] The present invention provides the composition ratios of Comparative Examples 1-6, as shown in Table 2 (in parts by weight):

[0176] The test results are shown in Table 3:

[0177] In the present invention, the warping degree is divided into four levels: severe warping, general warping, slight warping, and no warping. There is a range of values ​​in all test outlines, and the density requirement of PA6+GF30 is 1.35±0.02.

[0178] As shown in Tables 1 to 3, compared with Comparative Example 1, it can be seen from Comparative Example 5 that the introduction of glass beads to reduce the glass fiber content can balance the shrinkage rate of the composite material, but it will greatly reduce the strength of the composite material. While Example 2 ensures that the strength and specific gravity of the composite material remain basically unchanged, it balances the shrinkage rate of the composite material and reduces the warping degree of the product. It can be seen from Example 2 and Comparative Example 5 that when adding a suitable proportion of biomass-based carbon tubes, the specific gravity of the composite material will not be greatly changed, and the composite material produced is stronger than the method of replacing glass fiber with part of inorganic minerals.

[0179] It can be seen from Comparative Example 1 and Comparative Example 6 that the density of the composite material of Comparative Example 6 is 35% of the density of glass fiber (the main component is silica) filled with PA6, indicating that the biomass-based carbon tube is basically filled with silica. It can be seen from Comparative Example 6 and Example 2 that the composite product of Comparative Example 6 warps, while the composite product of Example 2 does not warp, indicating that the biomass-based carbon tube port forms an "anchor point" with the thermoplastic material, which will fasten the glass fiber in the anchor cage, and reduce the orientation of the glass fiber inside the composite material during injection molding, thereby reducing the warping degree of the product. The biomass-based carbon tube material port filled with silica does not form an "anchor point" with the material, causing the composite product of Comparative Example 6 to warp. And it can be clearly seen in Examples 1-4 that as the amount of biomass-based carbon tubes added increases, the "anchor point" formed by the biomass-based carbon tubes and the material also increases, so the warping degree of the composite material decreases. In addition, the performance data of the composite material reflects that the comprehensive performance is best when 5% of the biomass-based carbon tube material is added.

[0180] The difference between Comparative Example 2 and Example 2 is that the biomass-based carbon tube material has not been impregnated with a mixture of silane coupling agent and alcohol. From the final data, it can be seen that the strength, shrinkage rate, and warping degree are all inferior to those of Example 2 of the biomass-based carbon tube material impregnated with a mixture of coupling agent and alcohol (the compatibility of the biomass-based carbon tube with the resin is slightly poor without silane coupling agent treatment).

[0181] The difference between Comparative Examples 3 and 4 and Example 2 is that the aspect ratios of the biomass-based carbon tube materials are different. From the experimental results, the biomass-based carbon tube materials with high aspect ratios will have the same directional tendency as glass fibers, resulting in a large difference in the lateral and longitudinal shrinkage ratios of the materials and warping of the parts.

[0182] In the present invention, the test standards involved are:

[0183] Tensile strength: ISO 527,

[0184] Bending strength: ISO 178,

[0185] Density: ISO 1183,

[0186] Shrinkage Flow direction: ISO 294,

[0187] Shrinkage vertical direction: ISO 294.

[0188] Note that the above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention has been described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.

Claims

1. A method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material, characterized in that: The following steps are involved: A. Select biomass-based carbon tubes for treatment. The selected biomass-based carbon tubes have a length of 0.01-0.1 mm and are fibrous materials with a fiber diameter of 15-30 microns; The processing method of biomass-based carbon tubes is: A1. Place the biomass-based carbon tubes in a drying oven at 80°C and a vacuum degree of -0.08Mpa for 12 hours; A2. Mix the silane coupling agent with 99% alcohol in a ratio of 1:1 and stir for 5 minutes. A3, ultrasonically dispersing the biomass-based carbon tubes obtained in step A1 into the mixed solution of silane coupling agent and alcohol prepared in step A2, and uniformly dispersing by ultrasonication; A4, vacuum filter the biomass-based carbon tubes wrapped with the ratio liquid, and then put them into a vacuum oven at 65°C for 4 hours for standby use; B. Weigh a certain amount of thermoplastic resin and a certain amount of compatibilizer and put them into a stirring pot, stir for 5 minutes until they are evenly stirred; C. Add a certain amount of wetting agent into the stirring pot and stir for 5 minutes until it is evenly stirred; D. Add a certain amount of processing aids to the mixing pot, stir at a low speed for 5 minutes, stir evenly, and then add the mixed materials into the main feed loss-in-weight scale; E. The biomass-based carbon tubes and chopped glass fibers treated in step A are stirred evenly at a low speed and then added to a side-feed loss-in-weight scale. Since the biomass-based carbon tube fiber material is relatively light and cannot be fed smoothly, it is mixed with glass fibers for use; F. Set the feeding amount of each loss-in-weight scale, set the appropriate screw speed, start the auxiliary equipment, and carry out granulation production; In parts by weight, the thermoplastic resin is 50-70, the chopped glass fiber is 20-30, the compatibilizer is 3-5, the treated biomass-based carbon tube is 3-10, the processing aid is 0.5-1.5, and the wetting agent is 0.3-1.

2.

2. The method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material according to claim 1, characterized in that: In step A, the biomass-based carbon tubes are vascular bundle materials extracted from straw, bamboo and trees as basic raw materials.

3. The method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material according to claim 1, characterized in that: In step B, the thermoplastic resin is at least one of PP, PA, PC, PBT, PET, and ABS.

4. The method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material according to claim 1, characterized in that: In step C, the wetting agent is one of white oil, diffusion oil and silicone oil.

5. The method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material according to claim 1, characterized in that: Step D, the processing aid includes an antioxidant and a lubricant; wherein the antioxidant is composed of hindered phenols and phosphites, the hindered phenols and phosphites antioxidants are compounded in a ratio of 1:2, the hindered phenols are at least one of 1010, 1076, and 1098, and the phosphites are at least one of 168 and 626; the lubricant is at least one of EBS, PETS, stearic acid, stearate, and PE wax.

6. The method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material according to claim 1, characterized in that: In step E, the chopped glass fibers are alkali-free chopped glass fibers impregnated with a silane coupling agent and have a diameter of 9 microns to 14 microns.

7. The method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material according to claim 1, characterized in that: The compatibilizer is a substance with polar groups, specifically thermoplastic resin grafted with maleic anhydride, ethylene-acrylate-glycidyl methacrylate terpolymer, and acrylate grafted with ethylene elastomer.

8. The method for balancing the transverse and longitudinal shrinkage of a glass fiber reinforced thermoplastic composite material according to claim 1, characterized in that: In step F, the screw speed is 380-400 rpm.

Citation Information

Patent Citations

  • Low-warpage low-density glass fiber reinforced polylactic acid composite material and preparation method thereof

    CN112812526A

  • PC-ABS alloy material and preparation method thereof

    CN114292510A